2017
DOI: 10.11596/asiajot.13.7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Occupation-Based Home-Visit Program for Clients with Dementia and Caregivers: A Pilot Study

Abstract: Several studies have been implemented on home-visit occupational therapy based on activities or occupations for clients with dementia and their caregivers, but all have been conducted abroad; none have taken place in Japan. Therefore, we performed a pilot study of the effectiveness of an occupation-based home-visit program for clients with dementia and their caregivers using single cohort design. The results of our analysis of participants' (n = 9) data indicated that the home-visit program could improve the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[9] In terms of "Teaching skills or passing on experiences to others," it has been reported that being able to convey their experiences to the next generation is important for older persons. [23] From a psychological perspective, studies have indicated that when elderly people were able to use their remaining functions and could integrate their life experience meaningfully when looking to the future through accepting their past and present situation, there was a positive association with fewer symptoms of dementia, [24,25] and positive feelings have been shown to have positive psychological effects on subjective well-being, reducing the risk of dementia. [26] However, there were minor differences between the age groups.…”
Section: Discussionmentioning
confidence: 99%
“…[9] In terms of "Teaching skills or passing on experiences to others," it has been reported that being able to convey their experiences to the next generation is important for older persons. [23] From a psychological perspective, studies have indicated that when elderly people were able to use their remaining functions and could integrate their life experience meaningfully when looking to the future through accepting their past and present situation, there was a positive association with fewer symptoms of dementia, [24,25] and positive feelings have been shown to have positive psychological effects on subjective well-being, reducing the risk of dementia. [26] However, there were minor differences between the age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Other significant carer-related outcomes reported from home-based interventions included: improved carer quality of life at three months (Occupational Therapy in Parkinson's Disease/OTiP, RCT [Sturkenboom et al, 2014[Sturkenboom et al, , 2016) and significant increase in carer health-related quality of life (the Home-based Reablement Program/I-HARP, pilot study [Jeon et al, 2020]). The Alzheimer's Disease Multiple Intervention Trial by Callahan et al (2017) (ADMIT, RCT), a pilot study by Nishida et al (2017) and the Developing an Intervention for Fall-Related Injuries in Dementia (DIFRID, feasibility study) by Allan et al, (2019) reported no significant differences between groups for positive carer outcomes.…”
Section: Quantitative Carer Outcomes Home-based Interventionsmentioning
confidence: 99%